Does formal housing encourage settlement intention of rural migrants in Chinese cities? A structural equation model analysis - Liu, Zhilin; Wang, Yujun; Chen, Shaowei (Urban studies (Edinburgh, Scotland), 2017)
A growing body of literature has attempted to understand the social integration of rural migrants in Chinese cities, and specifically patterns and determinants of migrant settlement intention. However, few studies have directly investigated the role of housing access in migrant settlement in cities. Based on a 12-city migrant survey conducted in 2009, this paper adopts the structural equation modelling approach to delineate the causal relationship between housing access and migrant settlement intention.We found a positive correlation between access to formal housing and stronger settlement intention, but such relationship was more attributed to a sorting process in which rural migrants who are more willing to settle down strive to expand their access to formal housing. Meanwhile, controlling for sociodemographic variables, sociocultural attachment factors are more significant predictors of migrant settlement intention than economic opportunities and achievements. These findings imply the necessity of a combination of affordable housing policy and other social policy measures if the government hopes to achieve the goal of boosting permanent settlement of rural migrants in cities and towns.